Recessive mutations in the neuronal isoforms of DST, encoding dystonin, lead to abnormal actin cytoskeleton organization and HSAN type VI. Issue 1 (18th November 2018) - Fortugno, Paola; Angelucci, Francesco; Cestra, Gianluca; Camerota, Letizia; Ferraro, Angelo Salvatore; Cordisco, Sonia; Uccioli, Luigi; Castiglia, Daniele; De Angelis, Barbara; Kurth, Ingo; Kornak, Uwe; Brancati, Francesco
Abstract: Hereditary sensory and autonomic neuropathies (HSAN) are clinically and genetically heterogeneous disorders, characterized by a progressive sensory neuropathy often complicated by ulcers and amputations, with variable motor and autonomic involvement. Several pathways have been implicated in the pathogenesis of neuronal degeneration in HSAN, while recent observations point to an emerging role of cytoskeleton organization and function. Here, we report novel biallelic mutations in the DST gene encoding dystonin, a large cytolinker protein of the plakin family, in an adult form of HSAN type VI. Affected individuals harbored the premature termination codon variant p.(Lys4330*) in trans with the p.(Ala203Glu) change affecting a highly conserved residue in an isoform‐specific N‐terminal region of dystonin. Functional studies showed defects in actin cytoskeleton organization and consequent delayed cell adhesion, spreading and migration, while recombinant p.Ala203Glu dystonin loses the ability to bind actin. Our data aid in the clinical and molecular delineation of HSAN‐VI and suggest a central role for cell‐motility and cytoskeletal defects in its pathogenesis possibly interfering with the neuronal outgrowth and guidance processes. Abstract : Dystonin (encoded by DST ) is one of the largest proteins in humans and member of the plakin family of cytoskeleton linker protein. Mutations affecting its neuronal isoforms have been so far reported in only 2 families with highly discordant phenotypes of Hereditary Sensory and Autonomic Neuropathy (HSAN type VI). Here, we identified novel variants in DST as the genetic defects of HSAN‐VI and contribute to its clinical and molecular definition. Functional studies showed altered cell‐motility and cytoskeletal defects providing novel pathogenic mechanisms.